Rice Import Development in Indonesia - Quartina Pudjiastuti, Agnes; Mekse Korri Arisena, Gede; Keswari Krisnandika, Anak Agung (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Rice consumption in Indonesia has risen as the population increasing rapidly. The structure of the young age population will influence the amount of per capita of rice consumption. The rice cultivating and production will also determine whether or not it will fulfil the needs. The present research aimed at analyzing Indonesian rice import within the last decade (2010 – 2019). The research method used was a literature review. The research result shows that within the last 10 years, the width of the rice cultivating and production area have been declining as much as 1,8% and 1.6% respectively. However, the rice productivity rate is still in positive number at 2.0%. Eventhough the household consumption declined as much as 2% annually, apparently this was not enough for Indonesia to fulfil the needs internally. In short term period, an import would be a solution to fulfil the needs for domestic rice consumption. On the other hand, for a longer term, an import can be a problem because the rice trade balance with be disrupted. A small number of rice export volume will result in a rice trade balance deficit in Indonesia.